Multiplane experimental optical data encryption using phase only holography (2025)
ABSTRACT: In this paper, we demonstrate a scheme to encrypt multiplane scenes using an experimental joint transform correlator cryptosystem capable of full complex modulation, implemented with a single phase-only spatial light modulator. We use two different encoding algorithms to achieve full complex modulation of the input plane of the joint transform correlator cryptosystem, enabling the encryption of any complex optical field using arbitrary complex-valued encryption keys. Using the capabilities of this proposal, we demonstrate, for the first time to our knowledge, the experimental optical encryption of a multiplane scene composed of up to nine different 2D objects placed at different distances along the optical axis. This scheme is implemented using both double-phase encoding and binary amplitude encoding, and the performance with both encoding approaches is compared both numerically and experimentally. We show that binary amplitude encoding is superior to double-phase encoding, producing results with comparable or higher quality, particularly in the experimental case, and allowing the encryption of larger scenes than what is possible using double-phase encoding.